Electrically tunable Bragg gratings in single-mode polymer optical fiber - Kalli, Kyriacos; Dobb, Helen L.; Webb, David J.; Carroll, Karen E.; Komodromos, Michael; Themistos, Christos; Peng, Gangding; Fang, Qi; Boyd, Ian W. (My University, 2007)
We present what is to our knowledge the first demonstration of a tunable fiber Bragg grating device in polymer optical fiber that utilizes a thin-film resistive heater deposited on the surface of the fiber. The polymer fiber was coated via photochemical deposition of a Pd/Cu metallic layer with a procedure induced by vacuum-ultraviolet radiation at room temperature. The resulting device, when wavelength tuned via joule heating, underwent a wavelength shift of 2 nm for a moderate input power of 160 mW, a wavelength to input power coefficient of −13.4 pm/mW, and a time constant of 1.7 s−1.
Keywords: Plastic optical fibers; Microstructured polymer; Bragg gratings